Digital Transformation in Vocational Education: Development and Evaluation of a Project-Based E-Jobsheet for LAN Installation Integrated with Google Workspace - T Rahmilia Agraini; Muhammad Adri; Muhammad Giatman; Asrul Huda (STAI Hubbulwathan Duri, 2026)
Vocational education must equip students with practical competencies aligned with the digital and Fourth Industrial Revolution era. However, learning in vocational schools often faces limitations, including scarce digital media resources, weak integration of real-world projects, and minimal use of collaborative technologies.This study aimed to develop and evaluate a Project-Based E-Jobsheet for Local Area Network (LAN) installation integrated with Google Workspace to enhance learning in Computer and Network Engineering programs. The research employed the 4D development model: Define, Design, Develop, and Disseminate. Instrument validation was conducted using Aiken’s V, while practicality and effectiveness were assessed through user responses and learning outcome analysis.The E-Jobsheet demonstrated high validity in terms of media (0.836), content (0.809), and language (0.909). Practicality testing yielded a score of 85.36%, categorized as “very practical.” Effectiveness analysis showed a significant improvement in student learning outcomes (p = 0.003). Integration with Google Workspace tools (Docs, Sheets, and Forms) enabled efficient collaboration, structured feedback, and digital assessment.The findings indicate that the Project-Based E-Jobsheet is valid, practical, and effective in enhancing student engagement and learning outcomes. It supports constructivist learning through active, collaborative, and project-based approaches. Despite limitations such as single-site implementation and reliance on internet access, this study offers an adaptive digital solution to improve vocational education and better prepare students for technological advancements.